Influence of loan to deposit ratio (LDR), non-performing loan (NPL) and provision for losses of productive assets (PLPA) on return on asset (ROA) in BPR Jujur Arghadana period 2019-2023 - Maulani, Magfira Gifani; Suryaningprang, Andre; Herlinawati, Erna; Sudaryo, Yoyo (Institute of Computer Science (IOCS), 2024)
This research was conducted to analyze the influence of Loan to Deposit Ratio (LDR), Non-Performance Loans (NPL), and Allowance for Productive Asset Losses (PPAP) on Return on Assets (ROA) at BPR Honest Arghadana for the 2019-2023 period. The sampling technique was carried out using a purposive sampling method with the criteria of Honest BPR Arghadana which publishes complete financial reports every year for the 2019-2023 period. Before the analysis is carried out, analysis requirements are first tested including normality test, multicollinearity test, heteroscedasticity test and autocorrelation test. The data analysis technique was carried out using the multiple linear regression analysis method using the SPSS 21 program tool. Proving the hypothesis was carried out using the T test and F test. The results of the research simultaneously stated that LDR, NPL and PPAP together had an effect on ROA of 24, 3%. Meanwhile, partial research results state that the LDR, NPL and PPAP variables do not have a significant effect on ROA.